(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study is about the use of mHealth technology in a rural area of Haryana to understand its effectiveness in addressing health issues of Reproductive, Maternal, Newborn and Child Health (RMNCH). The research has looked at the problem from three angles: from the point of view of mHealth technology that is in use, the Frontline Health Workers (FHWs) and from the target groups of RMNCH. The Palwal district, in the Haryana State of India has been selected purposively as it is one among the backward districts of the State. A Primary Health Centre has been randomly selected for conducting the field study in 2019. The structured interview schedule was used to collect data from randomly selected respondents from FHWs and from expectant mothers and mothers of newborn children. The findings of the study have revealed that mHealth interventions are getting effective as most of the respondents favored the new technology. The study confirms the hypothesis that ‘mHealth technologies have allowed community health workers to keep records of mothers and their children even in rural areas where there are no health facilities’. However, there are many problems to be addressed to make the health system more responsive to the needs of RMNCH. Some of them are like the access to the smart phones along with proper internet connection and better training of the FHWs and more conscientization of expectant mothers.